Matematyka

Autorzy:Praca zbiorowa

Wydawnictwo:GWO

Rok wydania:2016

Zapisz wyrażenia, nie używając ... 4.38 gwiazdek na podstawie 13 opinii
  1. Gimnazjum
  2. 2 Klasa
  3. Matematyka

`a) \ x+(3x-y^2+7) = ul(x)+ul(3x) - y^2 + 7 = 4x -y^2 + 7`  

`b)\ -a+(2a -3b - 1) =-ul(a) + ul(2a) - 3b - 1 = a - 3b - 1`    

`c)\ -x^2 +(x^2 -x - 7 ) =-ul(x^2) + ul(x^2) - x - 7 = -x - 7 `   

`d)\ -b^3 -(b^3-b^2-b)=-ul(b^3) - ul(b^3)+b^2 + b = -2b^3 + b^2 +b`   

`e)\ (2a - 3b) + ( 4a - b) = ul(2a) - ul(ul(3b)) + ul(4a) - ul(ul(b)) = 6a - 4b`    

`f)\ -(x^2 -3x)+(x^2 + 3x) = -ul(ul(x^2)) + ul(3x) + ul(ul(x^2)) + ul(3x) = 6x`  

 

`g)\ (a +b -c) - (2a-b+2c) = ul(ul(a)) + ul(b)- c - ul(ul(2a)) + ul(b) - 2c = -a + 2b -3 c` 

`h)\ -(x^2-xy-z)-(-x^2+2xy+2z)=-ul(x^2)+ul(ul(xy))+z+ul(x^2)-ul(ul(2xy))-2z=-xy-z`